EFEKTIFITAS PELAKSANAAN LAYANAN BIMBINGAN KELOMPOK DALAM MENGATASI KESULITAN BELAJAR SISWA DI KELAS IX SMP. - Roise Siregar (Universitas Negeri Medan, 2020)
Abstract: Effectiveness of the implementation of Group Guidance Services in Overcoming Student Learning Difficulties in Class IX Middle School. The purpose of this study is to determine student learning difficulties can be overcome through group guidance services in class IX-5 SMP Negeri 1 Pancur Batu Academic Year 2018/2019. The procedure of this research was carried out using Classroom Action Research (CAR) which included four components namely planning, acting, observing and reflecting and evaluating. The subjects of this study were students of class IX-5 SMP Negeri 1 Pancur Batu, the total number of students was 36 people who had difficulty learning as many as 7 people. In addition to smart students, the number of male students is 7, the number of female students is 3. The results showed that it was determined overall that students could achieve an improvement seen from changes in cycle I to cycle II. If averaged in cycle I, a percentage of 52% was obtained, in cycle II it was 91%. Thus the implementation of group counseling can overcome student learning difficulties.Keywords: Learning Difficulties, Group Guidance.Abstrak: Efektifitas pelaksanaan Layanan Bimbingan Kelompok Dalam Mengatasi Kesulitan Belajar Siswa Di Kelas IX SMP. Tujuan penelitian ini adalah untuk mengetahui kesulitan belajar siswa dapat diatasi melalui layanan bimbingan kelompok di kelas IX-5 SMP Negeri 1 Pancur Batu Tahun Pelajaran 2018/2019. Prosedur penelitian ini dilakukan menggunakan Penelitian Tindakan Kelas (PTK) meliputi empat komponen yaitu perencanaan, tindakan, observasi dan refleksi serta evaluasi. Subjek penelitian ini adalah siswa kelas IX-5 SMP Negeri 1 Pancur Batu, jumlah siswa seluruhnya 36 orang yang mengalami kesulitan belajar sebanyak 7 orang. Di pariasi dengan siswa yang pintar, Jumlah siswa laki-laki 7 orang, jumlah siswi perempuan 3 orang. Hasil penelitian menunjukkan ditetapkan secara keseluruhan siswa dapat mencapai peningkatan dilihat dari adanya perubahan pada siklus I ke siklus II. Jika dirata-ratakan pada siklus I diperoleh persentase sebesar 52 %, pada siklus II mencapai 91 %. Dengan demikian pelaksanaan bimbingan kelompok dapat mengatasi kesulitan belajar siswa.Kata Kunci: Kesulitan Belajar, Bimbingan Kelompok.